New Species of Ascomycetes from Two Hypersaline Endorheic Lagoon Complexes in Zaragoza Province (Aragon Community, Spain) - María Barnés-Guirado; José F. Cano-Lira; Andrew N. Miller; Alberto M. Stchigel (Journal of Fungi)
Although certain hypersaline endorheic lagoons in Spain have been investigated to evaluate the composition, spatial structure, and ecological roles of their macro- and microbiota, the fungi inhabiting these niches remain largely unexplored. In this study, we isolated several microfungi from the Salada Grande de Chiprana and La Playa lagoons, located in the Saladas de Chiprana (Directed Natural Reserve and Ramsar Wetland) and the Saladas de Sástago–Bujaraloz (Ramsar Wetland), respectively. As a result of morphological characterization and phylogenetic analysis using four informative molecular markers, we report the discovery of two new species of the genus Montagnula (M.), M. globospora and M. terricola, as well as one new species of Monosporascus (Mo.), Mo. auratispora. Montagnula globospora, isolated from a sediment sample from Salada Grande de Chiprana lagoon, is the only species of the genus producing unicellular, globose ascospores inside cleistothecial ascomata with a cephalothecoid peridium. Montagnula terricola was originally isolated from a soil sample in Malawi (ex-type strain). However, we have also identified another strain of this species from a sediment sample collected at La Playa lagoon. The remarkable features of M. terricola are the production of non-cephalothecoid cleistothecial ascomata and bicellular, bi-cupulate ascospores. Regarding Mo. auratispora, it was isolated from sediments of Salada Grande de Chiprana and is characterized by the production of golden-brown ascospores that do not turn black with age. Also, due to the results of our phylogenetic analysis, we transferred Herpotrichia striatispora to the genus Montagnula, as M. striatispora, and Montangula jonessi to the new genus Neomontagnula (N.), as N. jonessi.